2020
DOI: 10.3847/1538-4357/ab6730
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Mass and Environment in the Quenching of Galaxies. II.

Abstract: We take advantage of an analytic model of galaxy formation coupled to the merger tree of an N-body simulation to study the roles of environment and stellar mass in the quenching of galaxies. The model has been originally set in order to provide the observed evolution of the stellar mass function as well as reasonable predictions of the star formation rate-stellar mass relation, from high redshift to the present time. We analyse the stellar mass and environmental quenching efficiencies and their dependence on s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 69 publications
4
31
0
Order By: Relevance
“…Alternately, this could be interpreted in terms of the quenching timescale, suggesting that massive satellites quench earlier than their lower mass counterparts. We note that this interpretation is at least qualitatively consistent 7 with those of Wetzel et al (2013); Rhee et al (2020), who also suggest a shorter quenching timescale for massive satellites (see also Contini et al 2020, who found similar results for cluster satellites at higher redshift).…”
Section: Quenching In the Coma Clustersupporting
confidence: 90%
“…Alternately, this could be interpreted in terms of the quenching timescale, suggesting that massive satellites quench earlier than their lower mass counterparts. We note that this interpretation is at least qualitatively consistent 7 with those of Wetzel et al (2013); Rhee et al (2020), who also suggest a shorter quenching timescale for massive satellites (see also Contini et al 2020, who found similar results for cluster satellites at higher redshift).…”
Section: Quenching In the Coma Clustersupporting
confidence: 90%
“…Figure 9 shows that the stellar masses for BSF galaxies with logM * = 10.2 are lower than those of RQ galaxies, which have logM * = 10.6. According to models by Contini et al (2020), environmental quenching efficiencies for these masses are 0.5 and 0.6, respectively. This means that the mass quenching efficiency is similarly low for both.…”
Section: Galaxy Evolution In the Supercluster And In The Cocoonmentioning
confidence: 99%
“…External processes depend on environmental densities, on galaxy orbital properties, and also on galaxy masses. They are most effective at lower redshifts and for intermediate mass galaxies (Contini et al 2020). Tidal interactions between galaxies are external processes and they can transform the morphology of galaxies significantly.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that the quenching processes that are driven by mass and environment are largely separable, at least in the local (z 1) Universe (Baldry et al 2006;Peng et al 2010;Muzzin et al 2012;Kovač et al 2014;Guglielmo et al 2015;van der Burg et al 2018). This is to say that there are no cross-terms; the effectiveness of environmental quenching does not depend on stellar mass, and the self/mass-quenching itself does not depend on the environment (but for different interpretations, see De Lucia et al 2012;Contini et al 2020). We note that the separability of these processes does not mean that they are physically unrelated processes; galaxies may quench due to shock heating of their cold gas component due to interactions with the hot (host) halo; this is generally referred to as "halo quenching", a process that may become efficient for both centrals and satellites in host-haloes M halo 10 12 M (Dekel & Birnboim 2006;Cattaneo et al 2008).…”
Section: Introductionmentioning
confidence: 99%